Chinese art and its encounter with the world - Clarke, David J. (David James), 1954- (Hong Kong University Press, 2011)
The book offers a bridge into the critical understanding of modern Chinese art through its encounter with the world beyond China's borders. David Clarke demonstrates Chinese art's interconnections with Western cultures while exploring its inherited cultural traditions and internal historical change. The first section deals with the cross-cultural trajectories of individual Chinese artists who traveled from China to the West and then returned. The focus then shifts from the movement of individual artists between cultures to the process by which specific genres of Western art have been interpret.